The Lego movie : junior novel - Howard, Kate (New York, NY : Scholastic Inc., 2014)
An ordinary Lego minifigure, mistakenly thought to be the extraordinary MasterBuilder, is recruited to join a quest to stop an evil Lego tyrant from gluing the universe together.
"From the screenplay by Phil Lord & Christopher Miller, story by Dan Hageman & Kevin Hageman and Phil Lord & Christopher Miller."
Keywords: LEGO toys -- Fiction; Adventure and adventurers -- Fiction